Decision support system for managing and determining international class program: Ga and AHP approach - Handarujati Handarujati (JOURNAL OF EDUCATION, 2010)
Indonesian higher education today is faced with serious challenges that will threaten the existence of some universities. An increasing international competition will require that universities take a progressive approach to attract enough students to ensure their survival. One way the universities must improve is in the quality of their administration management. While universities in Indonesia do not compare well internationally, steps can be taken to improve the quality. There are potential lessons to be learned from corporate experience in quality control management. The present study is aimed at achieving an alternative method, a hybrid model for managing and determining the proposed International class based on many criteria of academic performance in university. The model combines two different methods in decision support system: Analytical Hierarchy Process (AHP) and linear weightage model, the proposed model uses the AHP pairwise comparisons and the measure scale to generate the weights for the criteria which are much better and guarantee more fairly preference of criteria. Findings show that applying the system as decision-support facility for the management has resulted in significant acceleration of planning procedures and implementation, raised the overall effectiveness with respect to the underlying methodology and ultimately enabled more efficient academic administration